BUILDING A FRAMEWORK FOR ELECTION EDUCATION AMONG UNIVERSITY STUDENTS (Journal of Governance and Development (JGD), 2024)
This paper presents a framework for educating university students on political issues during elections, with a specific focus on the impact of the Undi18 campaign. This campaign enables 18-year-olds to vote or contest in elections and has had a significant effect on the democratic landscape in Malaysia, as evidenced by its implementation during the PRU-15 election. The framework comprises two critical components: (1) evaluating university students’ perspectives on elections in Malaysia, and (2) measuring the extent of university students’ knowledge about political issues during elections. The framework has been developed by reviewing the current literature on election education and is intended to be adaptable for use in various educational contexts and by instructors from different fields. The aim is to enhance the level of political awareness and engagement among university students and to promote the strengthening of democratic processes.